Children's Interest in TV Advertisements and their TV Viewing Behaviour - Divakar, Radhamani; Anjana Raju, Guntur (Indian Journal of Marketing, 2016)
Television today is the most powerful media used to convey all types of messages. It is found in every home, whether upper, middle, or low class of society. Television viewing is quite common these days. Children today spend a maximum of their free time watching television where they are exposed to a large number of advertisements. They watch almost 2-3 hours of television everyday, which includes their favourite cartoons and other programmes. The number of TV running homes has come a long way; more than 100 million TV households have been accounted for so far. Accessibility to television is increasing day by day and has been accepted by the society. A variety of programmes are available round the clock. Many targeted programmes and commercials on television are attracting more and more number of children towards it. Television viewing brings about cognitive development and conveys knowledge, skills, and information to children. It encourages learning and imparts overall awareness. It brings about both theoretical and concrete thinking and initiates change in behaviour and attitudes. Hence, the beneficial and adverse effects of television is a matter of great concern. Television viewing has negative impacts too. It may place children in passive roles. It dissuades them from reading, playing, exercising, studying, and so forth. It decreases actual social communication and develops violent and destructive behaviour in children (Gupta, Saini, Acharya&Miglani, 1994). This study was conducted to take note of TV viewing behaviour among children from urban and rural areas of Goa. A sample of 200 children of 6-12 years of age across Goa was selected. It was found that more number of children in rural areas watched advertisements as compared to their urban counterparts. On an average, children watched 2 hours or less of TV daily ; while on holidays, they watched TV for more than 3 hours. As age advances, children's interest towards television decreases. It was also observed that parents discussed about TV advertisements more with girls and older children and that too only when their children enquired about it from them.